Data for "The influence of different abiotic conditions on the concentrations of free and conjugated (masked) deoxynivalenol and zearalenone in stored wheat" - Oluwakayode, Abimbola; Greer, brett; Meneely, Julie; He, Qiqi; Sulyok, Michael; Krska, Rudolf; Medina, Angel (Cranfield University, 2024)
This study aims to examine the impact of storage conditions of water activities 0.93, 0.95, 0.98 aw and temperature 20-25 °C on (a) the concentrations of DON and ZEN and their respective glucosides/conjugates and (b) the concentrations of emerging mycotoxins in both naturally contaminated and irradiated wheat grains inoculated with Fusarium graminearum to ascertain any potential increases in toxicity in the wheat grains.
Keywords: mycotoxins in food'; 'mycotoxins extration'; 'wheat'; 'Deoxynivalenol Mycotoxin'; 'Masked Mycotoxin'; 'LCMS analysis'; 'zearalenone concentrations'